VEGFR2 and OPG genes modify the risk of subclinical coronary atherosclerosis in patients with familial hypercholesterolemia. (June 2019) - Miramontes-González, José Pablo; Usategui-Martín, Ricardo; Pérez de Isla, Leopoldo; Alonso, Rodrigo; Muñiz-Grijalvo, Ovidio; Díaz-Díaz, José Luis; Zambón, Daniel; Jiménez, Francisco Fuentes; Martín-Vallejo, Javier; Rodríguez Gude, Ana Elisa; Jiménez, David León; Padro, Teresa; et al.
Abstract: Background and aims: Heterozygous familial hypercholesterolemia (FH) is a genetic disorder characterized by high levels of low-density lipoprotein cholesterol (LDL-C). The magnitude of atherosclerotic cardiovascular disease (ASCVD) risk in FH patients is highly variable, and this can result from genetic factors. The aim of our study was to characterize whether polymorphisms in VEGFR2 and OPG genes could influence the expression of ASCVD in FH patients. Methods: We studied 318 FH patients from the SAFEHEART registry, without clinical diagnosis of ASCVD. A coronary tomographic angiography (CTA) was performed to determine and evaluate the presence of coronary stenosis and coronary artery calcium, as measured by coronary calcium score (CCS). Genotyping of OPG rs2073618 and VEGFR2 rs2071559 polymorphisms was performed using TaqMan 5′-exonuclease allelic discrimination assays. Results: Homozygous GG genotype and G allele of VEGFR2 rs2071559 polymorphism were associated with decreased risk of developing coronary artery stenosis. In the analysis of OPG rs2073618 and VEGFR2 rs2071559 polymorphisms, according to the presence of coronary artery calcium, we found significant differences in both polymorphisms. Homozygous GG genotype and G allele of VEGFR2 rs2071559 polymorphism were associated with decreased risk of accumulation of coronary artery calcium measured by CCS in CTA. Moreover, being a carrier of the GG genotype and G allele of the OPG rs2073618 polymorphism increased the risk of the presence of coronary artery calcium measured by CCS in CTA. Conclusions: Polymorphisms in VEGFR2 and OPG genes modify the risk of ASCVD in FH patients. Graphical abstract: Image 1 Highlights: OPG rs2073618 and VEGFR2 rs2071559 SNPs are associated with atherosclerotic cardiovascular disease. VEGFR2 rs2071559 SNP decreases risk of developing coronary artery stenosis. VEGFR2 rs2071559 SNP decreases risk of coronary artery calcium accumulation. OPG rs2073618 SNP increases the risk of the presence of coronary artery calcium.